Pengaruh Harga dan Kelengkapan Produk Terhadap Keputusan Pembelian di B2 Variasi Motor Jombang - Ahmad Zulkifli; Lik Anah (BIMA : Journal of Business and Innovation Management, 2021)
The purpose of this research is to examine the effect of price and product completeness on purchasing decisions. This research was conducted quantitatively, with a causal type. The population of this research is buyers in B2 Variasi Motor Jombang. Hypothesis testing uses the t test and f test, and uses the R2 test and multiple linear regression analysis. The results showed that: 1) Price partially affects the Purchase Decision, resulting in a probability value of 0.00. 2) Product completeness partially affects the purchasing decision resulting in a probability value of 0.00. 3). Meanwhile, price and product completeness have a simultaneous effect on purchasing decisions, with a probability value of 0.00. Keywords: Price, Product Completeness, Buying Decision